Treatment Of Epoxy Surface by DBD Cold Atmospheric - Qassem Mohammed, Noor; H Murbat , Hamid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The current study focuses on the surface modification of an air dielectric barrier discharge (DBD) at atmospheric pressure on a polymer (epoxy). Atomic force microscopy (AFM), Hardness and Thermo-gravimetric analysis (TGA), and Differential Scanning Calorimetry (DSC) were used to characterize the material. Plasma was used to expose the epoxy sample for (0, 10, 20, and 30 min). The AFM study shows an increase in the time of plasma treatment and an increase in the parameter of roughening, in which the surface of the material is roughened by the plasma treatment. This plasma-induced morphological modification of the epoxy surface will also contribute to enhancing the wettability. In the DSC test, the stability of the glass transition temperature was maintained until 20 minutes of plasma treatment. Still, at 30 minutes of plasma treatment, the glass transition temperature decreased, while the thermal stability of all exposure times in plasma was unaffected for the TGA test. It was found that epoxy improves its hardness after being treated with plasma at 10, 20, and 30 min, and the best plasma curing time was at 10 minutes. The hardness of the exposed epoxy to plasma remains at 20 and 30 min more than that of the control epoxy. The increase in the hardness of the epoxy after being treated with plasma is because it is a thermosetting material. The hardness of the epoxy improves when treated with plasma.